Institutional repository access policy in public university libraries in Central Java, Indonesia / MZ Eko Handoyo and Atin Istiarni - MZ, Eko Handoyo; Istiarni, Atin (2020)
This article discusses the repository as a service access policy developed and implemented in public university libraries, Central Java, which still protects intellectual work's rights. University-led policies, especially regarding the access of repository collection, becomes very important in this era, as concerning scientific works of academicians and the rights of one's intellectual work. This study aimed to analyze the policies, implementation barriers, and stakeholders' views on accessing the repository imposed in Central Java public university libraries. Samples were taken from ten libraries State University (PTN) in the province of Central Java, Indonesia. Qualitative research method using descriptive, by collecting data through questionnaires distributed to respondents, and study documents to support this research. The results showed that the state university library has a collection of the institutional repository that contains the scientific work community. The software used to manage repository generally uses software-based Eprints, Slmis (GPL v3), and others. Simultaneously, the repository's existing content includes scientific paper form, thesis, thesis, dissertations, and articles. While the policy of access to the collection in the library repository respondent is open access, open access part, and the access is closed, which is reinforced by the legal umbrella of Decree (SK) Rector, Standard Operating Procedure (SOP), or other policies. The head of the library's role in this regard is as a facilitator in developing policies on access to the repository collection.